Nanoreactors based on DNAzyme-functionalized magnetic nanoparticles activated by magnetic field. Issue 3 (3rd January 2018) - Bakshi, Saira F.; Guz, Nataliia; Zakharchenko, Andrey; Deng, Han; Tumanov, Alexei V.; Woodworth, Craig D.; Minko, Sergiy; Kolpashchikov, Dmitry M.; Katz, Evgeny
Abstract : A new biomimetic nanoreactor for analysis of mRNA cancer biomarkers is presented based on DNAzyme bound to superparamagnetic nanoparticles. Abstract : A new biomimetic nanoreactor design, MaBiDz, is presented based on a copolymer brush in combination with superparamagnetic nanoparticles. This cellular nanoreactor features two species of magnetic particles, each functionalized with two components of a binary deoxyribozyme system. In the presence of a target mRNA analyte and a magnetic field, the nanoreactor is assembled to form a biocompartment enclosed by the polymeric brush that enables catalytic function of the binary deoxyribozyme with enhanced kinetics. MaBiDz was demonstrated here as a cellular sensor for rapid detection and imaging of a target mRNA biomarker for metastatic breast cancer, and its function shows potential to be expanded as a biomimetic organelle that can downregulate the activity of a target mRNA biomarker.